Normal and sonographic anatomy of selected peripheral nerves. Part III: Peripheral nerves of the lower limb - Kowalska, Berta (J Ultrason, 2012)
The ultrasonographic examination is currently increasingly used in imaging peripheral nerves, serving to supplement the physical examination, electromyography and magnetic resonance imaging. As in the case of other USG imaging studies, the examination of peripheral nerves is non-invasive and well-tolerated by patients. The typical ultrasonographic picture of peripheral nerves as well as the examination technique have been discussed in part I of this article series, following the example of the median nerve. Part II of the series presented the normal anatomy and the technique for examining the peripheral nerves of the upper limb. This part of the article series focuses on the anatomy and technique for examining twelve normal peripheral nerves of the lower extremity: the iliohypogastric and ilioinguinal nerves, the lateral cutaneous nerve of the thigh, the pudendal, sciatic, tibial, sural, medial plantar, lateral plantar, common peroneal, deep peroneal and superficial peroneal nerves. It includes diagrams showing the proper positioning of the sonographic probe, plus USG images of the successively discussed nerves and their surrounding structures. The ultrasonographic appearance of the peripheral nerves in the lower limb is identical to the nerves in the upper limb. However, when imaging the lower extremity, convex probes are more often utilized, to capture deeply-seated nerves. The examination technique, similarly to that used in visualizing the nerves of upper extremity, consists of locating the nerve at a characteristic anatomic reference point and tracking it using the “elevator technique”. All 3 parts of the article series should serve as an introduction to a discussion of peripheral nerve pathologies, which will be presented in subsequent issues of the “Journal of Ultrasonography”.